2-Phosphonobutane-1, 2, 4-tricarboxylic acid (PBTCA) degradation by ozonation: Kinetics, phosphorus transformation, anti-precipitation property changes and phosphorus removal. (1st January 2019) - Xu, Zi-Bin; Wang, Wen-Long; Huang, Nan; Wu, Qian-Yuan; Lee, Min-Yong; Hu, Hong-Ying
Abstract: 2-Phosphonobutane-1, 2, 4-tricarboxylic acid (PBTCA) is an antiscalant that is widely used in reverse osmosis (RO) systems. Because of its high concentration in RO concentrate, eutrophication risk and anti-precipitation properties may affect subsequent treatments, therefore treatment strategies are needed to eliminate such substances. In this study, PBTCA was degraded by ozonation. The results show that PBTCA reacted with ozone molecules and hydroxyl radicals, with second-order rate constants of (0.12 ± 0.002) and (7.83 ± 1.51) × 10 8 L mol −1 s −1, respectively. The phosphorus in PBTCA (PP ) was transformed into organic phosphorus except for PBTCA (PO ), and inorganic phosphorus (PI ); PO was further transformed into PI . The changes in the concentrations of these phosphorus forms were investigated by model simulation. Simulation showed that the rate of PP transformation into PO was 5.5 times higher than that into PI . PBTCA was ozonated much faster at alkaline pH than at acidic pH. This is ascribed to different amounts of ozone molecules and hydroxyl radicals, and their different reaction rates with PBTCA. Furthermore, anti-precipitation property was reduced during ozonation, as shown by the amounts and morphology changes of the precipitates. PBTCA concentration for 50% anti-precipitation (AP50 ) did not change during ozonation, indicating that the transformation products generated during ozonation did not have anti-precipitation effects. Phosphorus in PBTCA was removed by ozonation–coagulation treatment. Total phosphorus and inorganic phosphorus were removed efficiently by using ferric chloride as a coagulant. The coagulants tended to bind with inorganic phosphorus to form flocs. Meanwhile, flocs were more easily to aggregate and precipitate as anti-precipitation effect was gradually removed, thus more phosphorus was removed. A combination of ozonation and coagulation removed PBTCA effectively and simultaneously reduced its anti-precipitation property and phosphorus. Graphical abstract: Highlights: PBTCA degradation kinetics by ozone molecule and hydroxyl radical was investigated for the first time. Phosphorus transformation during PBTCA ozonation was elucidated in details. Anti-precipitation property changes were evaluated during PBTCA ozonation. Anti-precipitation property of transformation products generated during PBTCA ozonation was analyzed. Ozonation-coagulation combination treatment was recommended in dealing with PBTCA.